2003
DOI: 10.1038/sj.cr.7290174
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mitochondrion-mediated apoptosis of CHO cells by tripchloro- lide

Abstract: Tripchlorolide (TC) is a potent antitumor reagent purified from a Chinese herb Tripterygium Wilfordii Hook. f.. However, its cellular effects and mechanism of action are unknown. We showed here that TC induced apoptosis of Chinese Hamster Ovary (CHO) cells in time-and dose-dependent manners. TC resulted in the degradation of Bcl-2, the translocation of Bax from the cytosol to mitochondria, and the release of cytochrome c from mitochondria. Stable overexpression of human Bcl-2 could reduce the apoptosis of TC-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Tripchlorolide (TC), a derivate of triptolide with similar activity and much lower toxicity [25], has shown its anti-neoplastic activities against leukemic, lung and other tumor cells. Our previous works reported that TC disturbed the cell cycle and induced apoptosis in Chinese hamster ovary (CHO) cells, which resulted from degradation of c-Myc and dysfunctional p53 [26,27]. In this study, we demonstrated that TC inhibited the expression of viral oncoprotein E6/E7, which resulted in an up-regulation of p53 in HeLa S3 cells.…”
Section: Introductionmentioning
confidence: 58%
“…Tripchlorolide (TC), a derivate of triptolide with similar activity and much lower toxicity [25], has shown its anti-neoplastic activities against leukemic, lung and other tumor cells. Our previous works reported that TC disturbed the cell cycle and induced apoptosis in Chinese hamster ovary (CHO) cells, which resulted from degradation of c-Myc and dysfunctional p53 [26,27]. In this study, we demonstrated that TC inhibited the expression of viral oncoprotein E6/E7, which resulted in an up-regulation of p53 in HeLa S3 cells.…”
Section: Introductionmentioning
confidence: 58%
“…14 MAPK, mitogen-activated protein kinase; TF, transcription factor; TNF-a, tumour necrosis factor-a; IL-1b, interleukin-1b. activating the mitochondrion-mediated apoptotic pathway involving Bcl-2 family proteins and cytochrome c. 77 Tripchlorolide was also shown to promote the degradation of c-Myc protein, an important oncogenic driver in many cancers. 78 …”
Section: Anti-cancer Properties Of Tw Bioactive Compoundsmentioning
confidence: 99%
“…A pivotal role of plants in the health scenario is attributed to bioactive compounds, which could delay or inhibit the inception of degenerative diseases and increase life expectancy (Jagadish et al 2009). Plant-based products exhibit anticancer potential by apoptosis induction, anti-angiogensis, accumulation of p53, suppression of NF-kB activation, cell-cycle arrest, topoisomerase inhibition, preventing the oxidation of DNA, triggering carcinogen-detoxifying system, hindering carcinogen activation (Chainy et al 2000;Ren et al 2003) and many other pathways. Hence, it is imperative to explore novel natural sources for their anticancer efficacy.…”
Section: Introductionmentioning
confidence: 99%